Can Gratitude Help to Craft Your Career? The Role of Prosocial Motivation and Intrinsic Motivation - Qing Zhang; Haibo Yu; Rui Xiong; Xiaolin Ge; Lei Gao (Behavioral Sciences, 2024)
Career crafting offers a new approach for individuals to cope with changing career situations. However, few studies have focused on personality-related antecedents that stably predict career proactivity. Additionally, as individuals’ careers are embedded in various social relationships, career crafting involves significant social interaction. Our study focuses on gratitude, which is related to social interaction, suggesting that gratitude fosters an appreciation for interpersonal relationships, providing a beneficial impetus for career crafting. A quantitative approach was adopted with a three-wave survey with 825 responses, and SPSS 26 and Mplus 8.3 were used as the analytical software for confirmatory factor analysis, hierarchical regression analysis, and path analysis. We conducted an empirical examination employing a moderated mediation model grounded in the framework of proactive motivation. The results revealed a positive correlation between gratitude and career crafting, with prosocial motivation mediating this relationship. Simultaneously, intrinsic motivation moderated the relationship between prosocial motivation and career crafting. Our study emphasizes gratitude’s role in career crafting and explores how it, along with prosocial motivations, drives proactive behaviors, responding to calls for relational work redesign and examining interactions between intrinsic and prosocial motivations in careers. It has important practical implications for individuals, organizations, and career counselors.